2012
DOI: 10.21273/hortsci.47.12.1698
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Selected Quality Attributes of Greenhouse Tomato Fruit as Affected by Pre- and Postharvest Environmental Conditions in Year-round Production

Abstract: ‘Durinta’ tomatoes were grown hydroponically using rockwool substrate in greenhouses to assess the seasonal and postharvest changes of selected quality attributes including lycopene and total soluble solids (TSS, % Brix) concentrations in fruit when grown under varied electrical conductivity (EC) in the nutrient solution. Two levels of EC examined in this study were 2.4 and 4.8 dS·m−1 for standard low EC and high EC treatments, respectively. All fruits at light-red and red ripeness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
(47 reference statements)
2
18
0
Order By: Relevance
“…Lycopene content was considerably enhanced (with an average growth of 6.3% between low and high EC treatment). These results are similar to those of other studies (Borghesi et al, 2011;De Pascale et al, 2001;Krauss et al, 2006;Kubota et al, 2012). However, EC reduced or had no effect on lycopene content, as previously reported (Ali and Ismail, 2014;Fern andez-García et al, 2002;Van Meulebroek et al, 2012).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Lycopene content was considerably enhanced (with an average growth of 6.3% between low and high EC treatment). These results are similar to those of other studies (Borghesi et al, 2011;De Pascale et al, 2001;Krauss et al, 2006;Kubota et al, 2012). However, EC reduced or had no effect on lycopene content, as previously reported (Ali and Ismail, 2014;Fern andez-García et al, 2002;Van Meulebroek et al, 2012).…”
Section: Resultssupporting
confidence: 93%
“…Total phenolics content and total antioxidants increased, with an average growth of 8.1% and 11.1%, respectively, between the low and high EC treatments. Previous studies found significant differences at extreme EC values (2-10 dS · m -1 ) (Krauss et al, 2006;Van Meulebroek et al, 2012;Zushi and Matsuzoe, 2015) or no differences at moderate EC values (Ali and Ismail, 2014;Kubota et al, 2012). This enhancement may be a response to increased reactive oxygen species linked to water stress level (Krauss et al, 2006).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Reduced water status and increased soil EC can increase sugar, titratable acids, and carotenoid concentrations in tomato fruits, which may contribute to the differences observed between greenhouse and fieldgrown tomato fruits in Expt. 1 (Kubota et al, 2012;Mitchell et al, 1991;Segura et al, 2009;Wu and Kubota, 2008;Yin et al, 2010). The differences between outdoorgrown and greenhouse tomatoes, as well as the lack of differences among greenhouse treatments, corroborated our sensory data as well as previous findings (Dzakovich et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…The quantity and composition of beneficial compounds present in tomato vary significantly depending on various plant specific factors and environmental conditions. Antioxidant properties of the fruit are influenced by genotype, degree of ripening, soil and climate conditions, part of the fruit, light, temperature, growing season, agricultural practices, and postharvest conditions (Kotikova et al, 2011;Oms-Oliu et al, 2011;Kubota et al, 2012;Vallverdu-Queralt et al, 2012;Tinyane et al, 2013;Kuscu et al, 2014;Vinha et al, 2014;Riga, 2015). Of these factors, genotype is one of the most important for determining the quantity of phytochemicals, and consequently for the overall quality of the tomato fruit.…”
Section: Introductionmentioning
confidence: 99%